HSP70 and TNF Loci Polymorphism Associated with the Posner-Schlossman Syndrome in a Southern Chinese Population - Wei Bai; Xiaosheng Huang; Xiaoli Shen; Ye Ye; Shiming Peng; Tianhui Zhu; Shaoyi Mei; Jiajie Kuang; Sejie Yu; Xiaochen Ma; Jun Zhao (Journal of Immunology Research)
Previous studies have shown that HLA gene polymorphisms are associated with the pathogenesis of the Posner-Schlossman syndrome (PSS). This study was aimed at evaluating the associations between HLA-III gene polymorphisms and PSS in a southern Chinese Han population. A total of 150 PSS patients and 183 healthy controls were included in this study. Twenty-one single nucleotide polymorphisms (SNPs) of HLA-III genes (including HSP70-1, HSP70-2, HSP70-hom, TNF-α, TNF-β, C2, and CFB) were genotyped using the SNaPshot technique. Our study showed that the frequencies of G allele at rs909253, A allele at rs1041981, and G allele at rs2844484 of TNF-β in the patient group were significantly higher than those in healthy controls (Corrected P Pc=0.040, OR=1.45; Pc=0.033, OR=1.45; Pc=0.045, OR=1.58, respectively). The frequency of T allele at rs12190359 of HSP70-1 was significantly lower in PSS patients than those in healthy controls (Pc=0.018 and OR=0.10). The frequencies of the CCT haplotype of HSP70-1 gene (rs1008438-rs562047-rs12190359) and the ACCCTTT haplotype of HSP70 gene (rs2227956-rs1043618-rs1008438-rs562047-rs12190359-rs2763979-rs6457452) were significantly lower in PSS patients than those in healthy controls (Pc=0.024, OR=0.10; Pc=0.048, OR=0.10, respectively). In conclusion, the G allele at rs909253, A allele at rs1041981, and G allele at rs2844484 of TNF-β gene might be risk factors for PSS, while the T allele at rs12190359 of HSP70-1 gene and specific haplotypes of the HSP70-1 and HSP70 genes might be protective factors for PSS.